(untitled) (UNIZIK Journal of Marketing, 2024)
This study investigated the influence of extrinsic religiosity on green purchase intention in Southeast, Nigeria: The role of environmental knowledge. Specifically, the study extended the theory of planned behaviour in examining whether extrinsic religiosity has a significant relationship with consumers’ purchase intention; and whether environmental knowledge mediates the relationship. A quantitative research was conducted using a survey research design. An online questionnaire in Google Document was used for data collection. Discriminant and convergent validity tests were conducted, and reliability was tested using composite reliability. Purposive sampling was used in distribution of questionnaire to a sample of 384 respondents. Partial Least Square (SMART 4) Structural Equation Modeling technique was used for inferential statistical analysis. Descriptive statistical analysis was carried out using tables, frequencies, mean, and standard deviation aided by SPSS version 25.0. Data analysis revealed that extrinsic religiosity has no significant relationship with green purchase intention in Southeast, Nigeria; however, environmental knowledge has a significant mediating effect on the relationship between extrinsic religiosity and green purchase intention in Southeast, Nigeria. Hence, it was concluded that there is no significant relationship between extrinsic religiosity and green purchase intention in Southeast Nigeria, while environmental knowledge significantly mediates the relationship. It was recommended among others that green marketing organizations should consider environmental knowledge, when designing promotional strategies for marketing their green products to improve their contribution in the preservation of the environment especially in Southeast Nigeria.